2014
DOI: 10.1093/humupd/dmu052
|View full text |Cite
|
Sign up to set email alerts
|

The role of seminal plasma for improved outcomes during in vitro fertilization treatment: review of the literature and meta-analysis

Abstract: There are significantly improved outcomes when women are exposed to seminal plasma around the time of ovum pick-up or embryo transfer, with statistical significance for clinical pregnancy but not for ongoing pregnancy/live birth rates being achieved. This meta-analysis is limited by the small number of studies of variable methodology. Further research is required to determine the effect on live birth rate; however, this meta-analysis indicates a significantly improved clinical pregnancy rate and a potential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 51 publications
3
70
0
4
Order By: Relevance
“…So far, this analysis only allows us to judge the effect of any kind of SP or semen exposure. To analyse if SP may be used as a therapy in conventional gonadotropin‐stimulated IVF, subgroup analyses according to type of intervention have been assessed …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So far, this analysis only allows us to judge the effect of any kind of SP or semen exposure. To analyse if SP may be used as a therapy in conventional gonadotropin‐stimulated IVF, subgroup analyses according to type of intervention have been assessed …”
Section: Discussionsupporting
confidence: 92%
“…Our study was in agreement with a prior review . Crawford et al, in a meta‐analysis of seven RCTs, found significantly improved outcomes when women were exposed to SP around the time of ovum pickup or embryo transfer.…”
Section: Discussionmentioning
confidence: 74%
“…In vitro fertilization (IVF) is an assisted reproductive technology (ART) that has given hope to thousands of infertile couples since the delivery of Louise Brown, the first baby to be born with this technology in 1978 [2]. Despite the progress in IVF technologies, the rate of success in achieving clinical pregnancy is still low and, furthermore, live birthrates remain disappointing [3]. According to a recent report by the Centre of Disease Control (CDC), only 33% of ART treatments lead to a pregnancy, and only 27% result in a live birth (https://www.cdc.gov/art/ reports/2014/national-summary.html).…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared the clinical pregnancy and live birth/ongoing pregnancy rate and found a statistically significant improvement in clinical pregnancy rate but no significant improvement in terms of ongoing pregnancy/live birth rates. However, they admitted that available data for the ongoing pregnancy/live birth rates were very limited, and the methodology and quality of the analyzed studies were variable (Crawford et al 2014). The positive effect of seminal plasma exposure on the clinical pregnancy rate in IVF patients might be explained by an increase in the number of Treg that has been associated with improved pregnancy rates in IVF patients .…”
Section: Therapeutic Potential Of Seminal Fluidmentioning
confidence: 99%